Member of Management Committee - Parmaxi, Antigoni (My University, 2026)
As member of the Management Committee (MC) I co-supervised and coordinated the implementation of the COST Action. More specifically, we worked on: (a) choosing the research topics; (b) advising on the direction which work should take; (c) drawing up detailed plans, arrangements for the distribution of tasks, and defining methods for the different phases of execution of the Action, which may also include the creation of specialised working groups; including the planning and follow up of the Actions budget; (d) coordinating the contributions of all participants; (e) keeping abreast of the research being done in the territory of the Parties and in other countries; (f) liaising with international bodies, when appropriate; (g) exchanging research results among the Parties, and disseminating these results, as appropriate, to a wider public, to an extent compatible with adequate safeguards for the interests of Parties, their competent public authorities or bodies and research contractors in respect of industrial property rights and commercially confidential material; (h) providing for the evaluation of the research carried out during the Action when drawing up the annual progress reports and the final report; (i) formulating recommendations for the future use of the results achieved by the Action. (j) formulating an opinion on an application for participation by a non-COST institution including a possible recommendation to the CSO to attach certain special conditions to its approval; (k) bringing to the attention of the CSO or the appropriate Domain Committee any proposed substantial change in the Action framework including requests for extension or prolongation.